Native and generic parallel programming environments on a transputer and a PowerPC platform - Hoekstra, A.G.; Sloot, P.M.A.; van der Linden, F.; van Muiswinkel, M.; Vesseur, J.J.J.; Hertzberger, L.O. (Concurrency (Chichester, England.), 1996)
Genericity of parallel programming environments, enabling development of portable parallel programs, is expected to result in performance penalties. Furthermore, programmability and tool support of programming environments are important issues if a choice between programming environments has to be made. In this paper we propose a methodology to compare native and generic parallel programming environments, taking into account such competing issues as portability and performance. As a case study, this paper compares the Iserver‐Occam, Parix, Express and PVM parallel programming environments on a 512‐node Parasytec GCel. Furthermore, we apply our methodology to compare Parix and PVM on a new architecture, a 32‐node Parsytec PowerXplorer, which is based on the PowerPC chip. In our approach we start with a representative application and isolate the basic (environment)‐dependent building blocks. These basic building blocks, which depend on floating‐point performance and communication capabilities of the environments, are analysed independently. We have measured point‐to‐point communication times, global communication times and floating‐point performance. All information is combined into a time complexity analysis, allowing comparison of the environments on different degrees of functionality. Together with demands for portability of the code and development time (i.e. programmability), an overall judgement of the environments is given.